Faktor-Faktor Manajemen Material dalam Percepatan Pelaksanaan Proyek Konstruksi Padang Pariaman - Andriani, Rini; Jumas, Dwifitra Y.; Rita, Eva (Universitas Batanghari, 2025)
In the implementation of construction projects, the application of material management shows an influence on the smoothness of project work time, therefore it is necessary to examine and describe what parts of material management have an influence and how much influence they have. Based on literature studies and interviews and the author's experience as a project actor, a study was conducted to obtain the most influential factors in accelerating the implementation time of construction projects in Padang Pariaman Regency. The study was conducted using a Likert scale questionnaire method which was distributed to project actors as respondents and after that validity, reliability and factor analysis were tested on respondents' answers using SPSS. The results of the study obtained 2 new factors related to project material management, namely the first factor of inventory and warehousing control and the second factor was the factor of selecting specifications and material scheduling. The results obtained were quite unexpected because the specification selection factor is rarely discussed and used as a consideration when discussing the project implementation time, however, with the emergence of this factor, we as project actors are aware that this specification selection factor is very important in accelerating construction work in the Padang Pariaman Regency area.